Genetic characterization of MDR genomic elements carrying two aac(6′)-aph(2″) genes in feline-derived clinical Enterococcus faecalis isolate - Li, Xue-Song; Qi, Yu; Li, Peng-hui; Xue, Jun-ze; Li, Xuan-yu; Muhammad, Inam; Li, Ya-zhuo; Zhu, Dao-mi; Ma, Ying; Kong, Ling-Cong; Ma, Hong-Xia (Frontiers in Microbiology, 2023)
Multidrug-resistant Enterococcus faecalis (E. faecalis) often cause intestinal infections in cats. The aim of this study was to investigate a multidrug-resistant E. faecalis isolate for plasmidic and chromosomal antimicrobial resistance and their genetic environment. E. faecalis strain ESC1 was obtained from the feces of a cat. Antimicrobial susceptibility testing was carried out using the broth microdilution method. Conjugation experiments were performed using Escherichia coli and Staphylococcus aureus as receptors. Complete sequences of chromosomal DNA and plasmids were generated by whole genome sequencing (WGS) and bioinformatics analysis for the presence of drug resistance genes and mobile elements. Multidrug-resistant E. faecalis ESC1 contained a chromosome and three plasmids. The amino acid at position 80 of the parC gene on the chromosome was mutated from serine to isoleucine, and hence the amino acid mutation at this site led to the resistance of ESC1 strain to fluoroquinolones. Eleven antibiotic resistance genes were located on two plasmids. We identified a novel composite transposon carrying two aminoglycoside resistance genes aac(6′)-aph(2″). This study reported the coexistence of a novel 5.4 kb composite transposon and a resistance plasmid with multiple homologous recombination in an isolate of E. faecalis ESC1. This data provides a basis for understanding the genomic signature and antimicrobial resistance mechanisms of this pathogen.